Pengaruh Harga Diri Terhadap Perilaku Social Climber Pada Mahasiswa Bimbingan dan Konseling Universitas Negeri Semarang - Musafa'ah, Iin; Sugiyo, Sugiyo (Konseling Edukasi : Journal of Guidance and Counseling, 2021)
The Effect of Self-Esteem on Social Climber Behavior in Guidance and Counseling Students, Semarang State University. This study aims at examining the influence of self-esteem on social climber behavior on Guidance and Counseling students at Universitas Negeri Semarang. These phenomena were related to the behavior of social climber. The most highlighted social climber behavior on students reflected in their lifestyle, e.g. their appearance and circle. This phenomenon happened because of the desire to get recognition from the surroundings. The research was a quantitative method using a psychological scale to collect the data. The results of this study showed that there was a significant relationship between self-esteem and social climber behavior on students. The results of this study are useful for Guidance and Counseling teachers to provide more innovation in conducting Guidance and Counseling services, especially in order to be able to guide individuals with social climber behavior to become individuals who want to accept themselves as they are.Keywords: Self-Esteem, Lifestyle, Social Climber Behavior